Levels of 8-OxodG Predict Hepatobiliary Pathology in Opisthorchis viverrini Endemic Settings in Thailand. - Prasert Saichua; Anna Yakovleva; Christine Kamamia; Amar R Jariwala; Jiraporn Sithithaworn; Banchob Sripa; Paul J Brindley; Thewarach Laha; Eimorn Mairiang; Chawalit Pairojkul; Narong Khuntikeo; Jason Mulvenna; et al. (Public Library of Science (PLoS), 2015)
Opisthorchis viverrini is distinct among helminth infections as it drives a chronic inflammatory response in the intrahepatic bile duct that progresses from advanced periductal fibrosis (APF) to cholangiocarcinoma (CCA). Extensive research shows that oxidative stress (OS) plays a critical role in the transition from chronic O. viverrini infection to CCA. OS also results in the excision of a modified DNA lesion (8-oxodG) into urine, the levels of which can be detected by immunoassay. Herein, we measured concentrations of urine 8-oxodG by immunoassay from the following four groups in the Khon Kaen Cancer Cohort study: (1) O. viverrini negative individuals, (2) O. viverrini positive individuals with no APF as determined by abdominal ultrasound, (3) O. viverrini positive individuals with APF as determined by abdominal ultrasound, and (4) O. viverrini induced cases of CCA. A logistic regression model was used to evaluate the utility of creatinine-adjusted urinary 8-oxodG among these groups, along with demographic, behavioral, and immunological risk factors. Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive accuracy of urinary 8-oxodG for APF and CCA. Elevated concentrations of 8-oxodG in urine positively associated with APF and CCA in a strongly dose-dependent manner. Urinary 8-oxodG concentrations also accurately predicted whether an individual presented with APF or CCA compared to O. viverrini infected individuals without these pathologies. In conclusion, urinary 8-oxodG is a robust 'candidate' biomarker of the progression of APF and CCA from chronic opisthorchiasis, which is indicative of the critical role that OS plays in both of these advanced hepatobiliary pathologies. The findings also confirm our previous observations that severe liver pathology occurs early and asymptomatically in residents of O. viverrini endemic regions, where individuals are infected for years (often decades) with this food-borne pathogen. These findings also contribute to an expanding literature on 8-oxodG in an easily accessible bodily fluid (e.g., urine) as a biomarker in the multistage process of inflammation, fibrogenesis, and infection-induced cancer.